Uji Daya Hambat Ekstrak Etanol Bintang Laut Bertanduk (Protoreaster nodosus) terhadap Bakteri Streptococcus sp. dan Candida albicans - Indria Hafizah; Sulastrianah Sulastrianah (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2015)
Starfish is a marine biota that have potency for used in human health. Protoreaster nodosus is species of starfish that commonly found in water of southeast Sulawesi and not widely used by local community. The aim of this study is to find out bioactive compound and to examine the antibacterial and antifungal bioactivity ethanol exract of Protoreaster nodosus. Thin Layer Chromatography (TLC) is used in bioactive compound assay and disk diffussion method is used to examine antibacterial and antifungal activity. Ethanol extract of Protoreaster nodosus is diluted into 2000 ppm, 4000 ppm, 8000 ppm, 16.000ppm and 32.000 ppm. As the result result of this study, ethanol extract of Protoreaster nodosus are positively containing alkaloid, steroid, saponin, flavonoid and tannin. The diameter of clear zone of disk containing extract in nutrient agar with Streptococcus sp are  4,4 mm, 5,4 mm, 6,7 mm, 9,4 mm dan 11,4 mm, consecutively. The diameter of clear zone of disk containing extract in potato dextrose agar with Candida albicans are 6,6 mm, 9,15 mm, 11,5 mm, 13,95 mm and 20,7 mm, consecutively. In the conclusion, ethanol extract of Protoreaster nodosus from Southeast Sulawesi containing alkaloid, steroid, saponin, flavonoid and tannin. The Antibacterial activity is strong in concentration of 32.000 ppm and the antifungal activity is strong in 32.000  ppm, 16.000 ppm, 8.000 ppm, 4000 ppm concentration. Keywords: Protoreaster nodosus, antibacterial activity, antifungal activity Streptococcus sp, Candida albicans, secondary metabolite